In vivo studies of nanostructure-based photosensitizers for photodynamic cancer therapy - Voon, S.H.; Kiew, L.V.; Lee, H.B.; Lim, S.H.; Noordin, M.I.; Kamkaew, A.; Burgess, K.; Chung, L.Y. (Wiley-VCH Verlag GmbH, 2014)
Animal models, particularly rodents, are major translational models for evaluating novel anticancer therapeutics. In this review, different types of nanostructure-based photosensitizers that have advanced into the in vivo evaluation stage for the photodynamic therapy (PDT) of cancer are described. This article focuses on the in vivo efficacies of the nanostructures as delivery agents and as energy transducers for photosensitizers in animal models. These materials are useful in overcoming solubility issues, lack of tumor specificity, and access to tumors deep in healthy tissue. At the end of this article, the opportunities made possible by these multiplexed nanostructure-based systems are summarized, as well as the considerable challenges associated with obtaining regulatory approval for such materials. The following questions are also addressed: (1) Is there a pressing demand for more nanoparticle materials? (2) What is the prognosis for regulatory approval of nanoparticles to be used in the clinic?